Shame Memories and Eating Psychopathology: The Buffering Effect of Self‐Compassion. (24th September 2014) - Ferreira, Cláudia; Matos, Marcela; Duarte, Cristiana; Pinto‐Gouveia, José
Abstract Objective Research suggests that self‐compassion may protect against shame in eating disorders. This study examines the association between shame memories, self‐compassion, self‐judgment and eating psychopathology severity and tests the moderator effect of self‐compassion on the relationships between shame memories and eating psychopathology. Method Participants were 34 patients with the diagnosis of an eating disorder, who were assessed using Eating Disorder Examination and the Shame Experiences Interview and self‐report instruments measuring the traumatic and centrality to identity features of shame memories, self‐compassion and self‐judgment. Results Self‐compassion was negatively correlated to shame memory features and eating psychopathology, and self‐judgment was positively associated with such variables. Self‐compassion had a moderator effect on the association between shame traumatic and central memories and eating psychopathology severity. Conclusion This is the first study to explore the buffering effect of self‐compassion against the pathogenic effects of shame memories on eating psychopathology severity in eating disorders, with relevant clinical and research implications. Copyright © 2014 John Wiley & Sons, Ltd and Eating Disorders Association.